Influence of Vitamin D3 Supplementation on Infliximab Effectiveness in Chinese Patients With Crohn's Disease: A Retrospective Cohort Study - Xia, Sheng-long; Min, Quan-jia; Shao, Xiao-xiao; Lin, Dao-po; Ma, Guo-long; Wu, Hao; Cao, Shu-guang; Jiang, Yi (Frontiers in Nutrition, 2021)
Background: It remains uncertain whether vitamin D3 (vitD3) supplementation is beneficial for remission of Crohn’s disease (CD). The influence of vitD3 supplementation on Infliximab (IFX) effectiveness was analyzed in Chinese CD patients. Methods: In this retrospective cohort study, moderate-to-severe CD patients, who were bio-naïve and prescribed with IFX treatment for at least 54 weeks, were recorded from January 2014 to December 2019. VitD3 supplementation was defined as patients additionally took oral vitD3 (125 IU/d) within 3 days after the first infusion and persisted in the whole follow-up period. Disease activity was assessed using Harvey-Bradshaw Index (HBI). Serum cytokine profiles (IL-2, IL-4, IL-6, IL-10, TNF-α and IFN-γ) were quantitatively analyzed in a subset of all patients at baseline and 54-week after intervention. Results: Among 73 enrolled patients, 37 took vitD3 regularly (D3-patients), the others (non-D3-patients) did not. At 54-week, the mean 25-hydroxyvitaminD level increased in D3-patients (20.33 ng/mL vs. 15.07 ng/mL, P<0.001). The clinical remission rate was higher in D3-patients compared to non-D3-patients (83.8% vs. 61.6%, P=0.030). The decrease of HBI from baseline to 54-week was more in D3-patients than non-D3-patients (7.41±3.0 vs. 6.28±2.75, P=0.023). Furthermore, vitD3 supplementation was independently related to the increase of remission rate at 54-week in D3-patients (β=-1.667, P=0.015). The benefit of vitD3 supplementation was significant only in patients with deficient vitD3 (all P<0.05), but not in non-deficient vitD3. A total of 9 patients (4 non-D3-patients and 5 D3-patients) were selected to determine serum cytokine profiles after 54-week IFX treatment. In non-D3-patients, the decreases of TNF-α and IL-6 at 54-week were more obvious than at baseline (P=0.032, 0.022, respectively). In D3-patients, however, only IL-10 increased at 54-week compared with its baseline value (P=0.037). Conclusions: VitD3 supplementation could improve IFX effectiveness in CD patients, especially for patients with vitD3 deficiency. This beneficial effect of vitD3 supplementation probably arose from the up-regulation of IL-10. Trial registration: NCT04606017.